A retrospective study of implant-abutment connections on crestal bone level. - Lin, M-I; Shen, Y-W; Huang, H-L; Hsu, J-T; Fuh, L-J (Journal of Dental Research)
This study compared the effects of external hex, internal octagon, and internal Morse taper implant-abutment connections on the peri-implant bone level before and after the occlusal loading of dental implants. Periapical radiographs of 103 implants (63 patients) placed between 2002 and 2010 were collected, digitized, standardized, and classified into groups based on the type of implant-abutment connection. These radiographs were then analyzed with image-processing software to measure the peri-implant crestal bone change during the healing phase (4 months after implant placement) and at loading phases 1 and 2 (3 and 6 months after occlusal loading, respectively). A generalized estimating equation method was employed for statistical analysis. The amount of peri-implant crestal bone change differed significantly among all time-phase pairs for all 3 types of implant-abutment connection, being greater in the healing phase than in loading phase 1 or 2. However, the peri-implant crestal bone change did not differ significantly among the 3 types of implant-abutment connections during the healing phase, loading phase 1, or loading phase 2. This retrospective clinical study reveals that the design of the implant-abutment connection appears to have no significant impact on short-term peri-implant crestal bone change.